Formation of Public Opinion Through Facebook: A Study on the 2024 General Election Campaign of Bangladesh | Formação da Opinião Pública através do Facebook: Um Estudo Sobre a Campanha Para as Eleições Gerais de 2024 no Bangladesh - Md Fakrul Islam; Md. Hafizul Islam (Political Observer)
Facebook has become a pivotal platform for political propagandists. Since it can be used as a very convenient medium. Facebook, a political participation and conversation center, keeps becoming Bangladesh’s most popular social networking site. This study explores how Facebook usage influences the political perceptions of Bangladeshi people during the 2024 general election campaign. By focusing on a specific demographic (e.g., age, parliamentary constituency, gender, occupation), the study investigates relationships between Facebook interactions, exposure to political content, and their influence on shaping political opinion. Using a mixed-methods approach, findings suggest that interaction with political figures and exposure to diverse political content can shape public perceptions. However, the emotional and often spontaneous nature of reactions highlights the nuanced role of Facebook as a tool for political engagement and discourse.